2021
DOI: 10.17645/si.v9i1.3706
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing and Decision-Making: Attempts by Ghanaian Return Migrants to Enter through Libya

Abstract: This article examines the relationship between irregular migration, access to information and migration decisions. Using semi-structured interviews of thirty irregular return migrants who failed to reach their European destinations through Libya, I show that irregular return migrants from Ghana rely predominantly on interpersonal sources, including colleagues, neighbors, friends and relatives, for information on migration. Return migrants seek information from those who have relevant experience with that kind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In others, the knowledge transferred by these campaigns ‘from above’ may be undermined or contested by competing claims to knowledge sought and found elsewhere. Research shows that migrants' awareness of potential routes and destinations is often based, at least in part, on rumour and anecdotal information provided by family, friends, acquaintances and brokers—both before departure and whilst on the move (Crawley et al, 2018; Hagen‐Zanker & Mallett, 2016; Koomson‐Yalley, 2021; Lyberaki et al, 2008). Though the information provided through these means can be of varying quality and accuracy, as some of the above examples from Ethiopia show, it can nonetheless prove influential in guiding people's choices.…”
Section: Inside the Efficacy Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…In others, the knowledge transferred by these campaigns ‘from above’ may be undermined or contested by competing claims to knowledge sought and found elsewhere. Research shows that migrants' awareness of potential routes and destinations is often based, at least in part, on rumour and anecdotal information provided by family, friends, acquaintances and brokers—both before departure and whilst on the move (Crawley et al, 2018; Hagen‐Zanker & Mallett, 2016; Koomson‐Yalley, 2021; Lyberaki et al, 2008). Though the information provided through these means can be of varying quality and accuracy, as some of the above examples from Ethiopia show, it can nonetheless prove influential in guiding people's choices.…”
Section: Inside the Efficacy Gapmentioning
confidence: 99%
“…Our findings from this study about the role that known social connections can play in enhancing the legitimacy of certain kinds of information—particularly when those are connections with whom the individual already shares a relationship of (at least some) trust, including friends, family members, travelling companions or even a smuggler who came recommended (Hagen‐Zanker & Mallett, 2016)—are mirrored in a wider analysis of the link between the source of information and extent of trustworthiness. For example, one recent study into irregular migration from Ghana found that information about travelling to Europe via dangerous routes is often shared in the form of ‘funny stories’, strengthening the relationship between mediator and migrant and thus deepening the trustworthiness of the information shared (Koomson‐Yalley, 2021).…”
Section: Inside the Efficacy Gapmentioning
confidence: 99%
See 1 more Smart Citation